Determining an Evidence Base for Particular Fields of Educational Practice: A Systematic Review of Meta-Analyses on Effective Mathematics and Science Teaching - Knogler, Maximilian; Hetmanek, Andreas; Seidel, Tina (Frontiers in Psychology, 2022)
The call for evidence-based practice in education emphasizes the need for research to provide evidence for particular fields of educational practice. With this systematic literature review we summarize and analyze aggregated effectiveness information from 41 meta-analyses published between 2004 and 2019 to inform evidence-based practice in a particular field. In line with target specifications in education that are provided for a certain school subject and educational level, we developed and adopted a selection heuristic for filtering aggregated effect sizes specific to both science and mathematics education and the secondary student population. The results include 78 context-specific aggregated effect sizes based on data from over one million students. The findings encompass a multitude of different teaching strategies, most of which offer a measurable advantage to alternatives. Findings demonstrate that context-specific effect size information may often differ from more general effect size information on teaching effectiveness and adherence to quality standards varies in sampled meta-analyses. Thus, although meta-analytic research has strongly developed over the last few years, providing context-specific and high-quality evidence still needs to be a focus in the field of secondary mathematics and science teaching and beyond.